SILI-MUSA-YESUS:SUATU UPAYA KRISTOLOGI MENUJU KRISTOPRAKSIS - Dominicus Waso (STIPAS St. Sirilus Ruteng, 2013)
Ancestor worship is of course a religious phenomenon, it is part and parcel of a complex of beliefs,attitudes, obligations,social relations, ect., centered around the ancestors.If the attitude towards the ancestors is of such basic importance then there can hardly be any doubt that the Church in her effort to bring the Gospel to the Ngada people cannot afford to disregard it.The article tries to show an effort how mithological figures could be used as a locus for interpreting Jesus as the founder and the beginner of a customary and human tradition. Sili as has been exposed as the initiator the festival “Reba” in Ngada is partially used by this article to undesrtand and comprehend Jesus as the peak figure in renewing tradition. The article is an effort in constructing local theology, using a traditional terms and figure but giving it a new interpretation and new meaning.